FRENCH REVOLUTION: THE INFLUENCE OF 18TH CENTURY THINKERS (1700-1789) - Pinho de Rezende, Erickson; da Silva Lopes, Aldonei (Revista Gênero e Interdisciplinaridade, 2023)
This work has as objective, to verify as the French society thought the French Revolution, in the century XVIII. The used methodology was of specific bibliographies on the subject. The French society of the century XVIII was estratified and nested, divided in clergy, nobility and bourgeoisie. The French Revolution was the most important event of the Modern Era, marking the beginning of the Contemporary Time. The French Revolution had felt own, manifested in the taking of the power by the bourgeoisie, in the peasants’ active participation and artisans, in the surpass of the feudal institutions of the Old Regime and in the preparation of France for the walk in direction to the industrial capitalism. The politics in the France prérevolutionary showed the signs of absolute other Reis’ accumulated decadence, mainly a chronic deficit in the reign Luís XVI, that arose to the throne in 1774.